(U-Th)/He ages from zircons collected in the far western Nepal Himalaya - Mary Braza; Nadine McQuarrie; Delores M Robinson; Laura E Webb (PANGAEA, 2023)
This dataset contains the results of 11 individual (U-Th)/He analyses using zircons extracted from bedrock samples collected from medium-high grade metamorphic rocks along the Api transect in the far western Nepal Himalaya. Bedrock samples were collected for thermochronologic cooling ages to better constrain the exhumation history of the Nepal Himalaya. Analytical methods followed the general procedures outlined in Reiners (2005) and Reiners et al. (2004). The Full ZHe Data Raw contains results for each zircon grain measurement (typically three per sample). The ZHe Data Summary includes the mean age for each samples, calculated from three zircon grains, and an error that spans the range in measured ages and includes a 2σ analytical error.